Patientens delaktighet i val av vårdgivare. En litteratur review - Nilsson, Madeleine; Lindwall, Lillemor; Nilsson, Jan; From, Ingrid (Nordisk tidsskrift for helseforskning, 2018)
The idea behind care choice is that healthcare providers would be more responsive to patients’ health problems and needs and in doing so compete with increased quality and that patients should be able to choose from this. The question is how patients choose a healthcare provider by themselves. The aim was to describe what affected when patients chose healthcare providers. A literature review was carried out. The results showed that patients’ choice of healthcare providers depended on the following three themes: their own care experiences, caring relationships with staff and service provided by caregivers. The underlying idea of care choice is competition based on quality of care, but the results show that patients make their choices based on other factors as described in the result and therefore improvement can be achieved if focus is placed on being responsive for patient care needs. patient participation; primary care; caring needs; qualtiy of care; care choice; caring science pasientdeltakelse; primæromsorg; omsorgsbehov; kvalitet på omsorg; omsorg valg; omsorgsfull vitenskap